Inflammatory Protein Profiles in Plasma of Candidaemia Patients and the Contribution of Host Genetics to Their Variability - Matzaraki, Vasiliki; Le, Kieu T. T.; Jaeger, Martin; Aguirre-Gamboa, Raúl; Johnson, Melissa D.; Sanna, Serena; Rosati, Diletta; Franke, Lude; Zhernakova, Alexandra; Fu, Jingyuan; Withoff, Sebo; Jonkers, Iris; et al. (Frontiers in Immunology, 2021)
Circulatory inflammatory proteins play a significant role in anti-Candida host immune defence. However, little is known about the genetic variation that contributes to the variability of inflammatory responses in response to C. albicans. To systematically characterize inflammatory responses in Candida infection, we profiled 91 circulatory inflammatory proteins in 45 candidaemia patients. Given the significant differences in inflammatory protein profiles between patient and healthy individuals, we correlated genome-wide single nucleotide polymorphism (SNP) genotypes with protein abundance (protein quantitative trait loci, pQTLs) produced by peripheral blood mononuclear cells, stimulated with C. albicans yeast, from 378 individuals of European origin from the 500 Functional Genomics (500FG) cohort of the Human Functional Genomics Project and Lifelines Deep cohort. Furthermore, we investigated whether differences in survival of candidaemia patients can be explained by modulating levels of inflammatory proteins. We identified five genome-wide significant pQTLs modulated IL-8, MCP-2, MMP-1, and CCL3 in response to C. albicans. In addition, our genetic analysis suggested that GADD45G from rs10114707 locus that reached genome-wide significance could be a potential core gene that regulates a cytokine network upon Candida infection. Last but not least, we observed that a trans-pQTL marked from SNP rs7651677 at chromosome 3 that influences uPA is strongly associated with patient survival (Psurvival = 3.52 x 10-5, OR 3). Overall, our genetic analysis showed that genetic variation determines the protein abundance of circulatory proteins in response to Candida infection.